Neuronal and glial structural plasticity induced by drugs of abuse - M Foster Olive (Frontiers Research Topics, 2015)
Drugs of abuse induce a host of alterations in brain structure and function, ranging from changes in gene expression and epigenetic processes to aberrant synaptic plasticity to volumetric changes in discrete brain regions. These alterations can be drug class-specific, and are not confined to neurons, as drugs of abuse also induce molecular and cellular alterations in various glial cell types such as astrocytes and microglia. The phenomenon of drug-induced plasticity includes changes in dendritic branching and architecture, dendritic spine density and morphology, astrocyte-neuronal interactions, dysregulation of glutamatergic and GABAergic signaling, and alterations in myelination or microglial phenotype. This drug-induced "rewiring" of the brain at numerous levels can contribute to the development, maintenance, and persistence of the addicted state, as well as associated deficits in normal cognitive functioning. The aim of this Research Topic is to collect recent and important findings related to the structural alterations produced by drug of abuse in neurons, glial, and other cell types of the central nervous system.